2013
DOI: 10.1002/hc.21069
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Precursors of 4‐Phosphino‐1H‐pyrrole‐3‐carbaldehyde Derivatives

Abstract: In this work, possible approaches to the synthesis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Tris­( N -pyrrolyl)­phosphine , is a weak electron donor and good π-acceptor ligand, which has been successfully applied in hydroformylation reactions. The C2-connected structural isomer, tris­(1-methylpyrrol-2-yl)­phosphine, was first reported in 1974, followed by several derivatives of (1-methylpyrrol-2-yl)­phosphines. Yet, the properties of these phosphines have barely been investigated. , Among them, the cataCXium ligands represent a prominent class of N -arylated pyrrolylphosphines, which have been used in Suzuki cross-coupling reactions . Few reports exist about C3-bound pyrrolylphosphines. ,, In fact, the only representative with three pyrrolyl groups, tris­(1- tert -butylpyrrol-3-yl)­phosphine, has been generated in situ but was not isolated, and the electronic properties were not investigated . Note that the structurally related (indol-3-yl)­phosphines are powerful ligands for Pd-catalyzed cross-coupling reactions. , Herein, we report the synthesis and properties of a series of (1,2,5-trimethylpyrrolyl)­phosphines that, consistent with Zipse’s prediction, are strongly electron-donating arylphosphines.…”
Section: Introductionmentioning
confidence: 99%
“…Tris­( N -pyrrolyl)­phosphine , is a weak electron donor and good π-acceptor ligand, which has been successfully applied in hydroformylation reactions. The C2-connected structural isomer, tris­(1-methylpyrrol-2-yl)­phosphine, was first reported in 1974, followed by several derivatives of (1-methylpyrrol-2-yl)­phosphines. Yet, the properties of these phosphines have barely been investigated. , Among them, the cataCXium ligands represent a prominent class of N -arylated pyrrolylphosphines, which have been used in Suzuki cross-coupling reactions . Few reports exist about C3-bound pyrrolylphosphines. ,, In fact, the only representative with three pyrrolyl groups, tris­(1- tert -butylpyrrol-3-yl)­phosphine, has been generated in situ but was not isolated, and the electronic properties were not investigated . Note that the structurally related (indol-3-yl)­phosphines are powerful ligands for Pd-catalyzed cross-coupling reactions. , Herein, we report the synthesis and properties of a series of (1,2,5-trimethylpyrrolyl)­phosphines that, consistent with Zipse’s prediction, are strongly electron-donating arylphosphines.…”
Section: Introductionmentioning
confidence: 99%
“…N ‐substituted pyrroles are known to be readily phosphanylated with phosphane halides, affording phosphanes III (X = lone pair), which are potential substrates for further electrophilic formylation. Recently, we have shown that formylation of phosphane III (X = lone pair) and its derivatives (X = O, S, Se) under Vilsmeier–Haack conditions led to the same product— phosphane oxides IV .…”
Section: Introductionmentioning
confidence: 98%